Distributional signatures of depositional system of Pinghu Formation, Pinghu slope, Xihu Sag, East China Sea Shelf Basin - Zhongyun CHEN; Xuebin DU; Shuai LI (Shiyou shiyan dizhi, 2022)
The Eocene Pinghu Formation on the Pinghu slope of Xihu Sag of East China Sea Shelf Basin is a main confirmed strata for hydrocarbon enrichment. At present, many studies have been carried out on its sedimentary system, but certain controversies are still existed. On the basis of previous studies and newly processed 3D seismic, core and geochemical data, it was re-analyzed in this paper for the sedimentary system of Pinghu Formation. Results show that there are three types of sedimentary system on the slope belt: river-controlled delta, tidal-transformed delta and tidal flat depositional system. These three types of sedimentary modes have obvious zoning characteristics in plane. The northern area is dominated by river-controlled delta deposits. The middle area is dominated by tidal-transformed delta deposits. The southern area is in the mouth of a semi-closed bay, dominated by tidal flat system, and ocean currents control the spatial distribution shape and scale of sand bodies. It is concluded that the influence of seawater on the sedimentary pattern of the Pinghu Formation in the slope belt is strengthening from north to south.